Այգեգործական ֆրեզ-մեքենայի արտաշարժ օրգանի շարժաթևի և դրա շարժաբերման մեխանիզմի օպտիմալ պարամետրերի հիմնավորում - Պապյան, Սերյոժա; Հարությունյան, Գևորգ (ՀԱԱՀ հիմնադրամ)
Основным недостатком почвообрабатывающих машин для межствольного и приствольного пространства садов является невозможность обработки приствольных полос путем обхода отклоненных от ряда стволов деревьев. В результате исследований и наблюдений установлено, что поршень гидроцилиндра системы управления выносного рабочего органа следует фиксировать и в промежуточных положениях в зависимости от суммарной величины ширины защитной зоны растений, диаметра ствола дерева и его отклонения от оси ряда. Была составлена соответствующая расчетная схема, выведена функциональная связь между указанной суммарной величиной, шагом поршня гидроцилиндра и углом поворота рабочего органа, определены диапазоны регулирования гидроцилиндра в промежуточных положениях. The main disadvantage of garden tillage machines is the impossibility of cultivating tree trunk strips – by passing tree trunks deviated from a row, the reason for which is the inability to fix the piston of the hydraulic cylinder of the control system of the working body in intermediate positions. In this regard, in order to eliminate the above-mentioned drawback, a calculation diagram was drawn up and a functional relationship was derived between the diameter of the trunk, the deviation of the tree from the axis of the row, the width of the protective zone and the pitch of the hydraulic cylinder piston, as well as the angle of rotation of the working element/part. The intervals of changes in these quantities are determined, according to which it is necessary to fix the hydraulic cylinder piston in intermediate positions. It was found out that for precise interaction between the probe and the working organ, it is necessary to adjust the signal moment according to the intermediate positions of the hydraulic cylinder, based on the following values Si = 3.55-11.5 cm, φi = 9.970 – 30.60: ensuring the condition bi+fi+0.5(di+dա)≤Lmax.
Keywords: Ագրարային ճարտարագիտություն